Personified approach to diagnostics and treatment of atrial fibrillation. Diagnostic stage (part 1) - E. A. Praskurnichii; O. I. Morozova (Лечащий Врач)
The article presents a review of mechanisms, diagnostics and possible predictors of atrial fibrillation recurrence, as well as the analysis of available scientifically proved therapeutic approaches to the treatment of patients with this arrhythmia. The role of anticoagulant therapy both in the context of the strategy of «rate control» and in the use of the strategy of «rhythm control» is examined.